Imaging Hepatocellular Carcinoma With 68Ga-Citrate PET: First Clinical Experience. (8th September 2017) - Mari Aparici, Carina; Behr, Spencer C.; Seo, Youngho; Kelley, R. Kate; Corvera, Carlos; Gao, Kenneth T.; Aggarwal, Rahul; Evans, Michael J.
While cross-sectional imaging with computed tomography (CT) and magnetic resonance imaging is the primary method for diagnosing hepatocellular carcinoma (HCC), they provide little biological insight into this molecularly heterogeneous disease. Nuclear imaging tools that can detect molecular subsets of tumors could greatly improve diagnosis and management of HCC. To this end, we conducted a patient study to determine whether HCC can be resolved using 68 Ga-citrate positron emission tomography (PET). One patient with recurrent HCC was injected with 300 MBq of 68 Ga-citrate and imaged with PET/CT 249 minutes post injection. Four (28%) of 14 hepatic lesions were avid for 68 Ga-citrate. One extrahepatic lesion was not PET avid. The average maximum standardized uptake value (SUVmax ) for the lesions was 7.2 (range: 6.2-8.4), while the SUVmax of the normal liver parenchyma was 4.7 and blood pool was 5.7. The avid lesions were not significantly larger than the quiescent lesions, and a prior contrast CT showed uniform enhancement among the lesions, suggesting that tumor signals are due to specific binding of the radiotracer to the transferrin receptor, rather than enhanced vascularity in the tumor microenvironment. Further studies are required in a larger patient cohort to verify the molecular basis of radiotracer uptake and the clinical utility of this tool.